Updated ILAE Review of Antiepileptic Drug Efficacy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
The International League Against Epilepsy (ILAE) Subcommission on AED Guidelines reviewed the literature from July 2005 to March 2012 and combined results with previous analysis (2006) to provide a comprehensive update of level of AED efficacy as initial monotherapy with newly diagnosed or untreated epilepsy.